If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 38 = -4 Reorder the terms: 38 + 7x = -4 Solving 38 + 7x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + 7x = -4 + -38 Combine like terms: 38 + -38 = 0 0 + 7x = -4 + -38 7x = -4 + -38 Combine like terms: -4 + -38 = -42 7x = -42 Divide each side by '7'. x = -6 Simplifying x = -6
| 11(16-g)=22 | | f=-2f-9 | | -84-8x=9x+18 | | 156-7x=29x+24 | | 145-6x=3x+10 | | 8f=-2f-10 | | 9x=125 | | 2a+12=6 | | 7x=-64 | | 7x+32=-32 | | x=5000 | | a+6=4 | | x=2100 | | 12+56= | | 6=9x | | 0=9x-6 | | -16=8x | | 23=18+5x | | e=9-2e | | 4x=6x-11 | | 40=41+x | | 18y-6=-18 | | 18y-6=-10 | | 6p-5=7 | | 30=15x | | t=15x | | 6y^3-7y^2-7y+6=0 | | 20z-1+36=5z+5 | | 30-x=10+0.5x | | 11=21a | | 6m=x | | 4(-2z-5)-7=10 |